SOIL SALINITY OF THE SVETLOYAR IRRIGATED MASSIF IN THE VOLGOGRAD REGION IN 2010-S YEARS - I. N. Gorokhova; N. B. Khitrov; E. I. Pankova; K. O. Prokopyeva (Бюллетень Почвенного института им. В.В. Докучаева, 2018)
Results of salinity assessment of irrigated soils at the Svetloyar Irrigated Mas-sive located in the Northern Sarpa Lowland (Volgograd region) are shown. Soil cover patterns suffered severe transformation under the impact of ameliorative activity during 45–50-year irrigation. There were 25–50% of Solonetz and sol-onetzic soils on the investigated territory before the construction of Svetloyarsk Irrigation System. In 2010-s there were practically no Solonetz soils, as the main part of solonetzic (nitric) horizons were cut and mixed with material of other upper horizons during the planning works. Soil cover patterns of irrigated massive presented by transformed solonetz complex with solonchakous (epiprotosalic in WRB-2015) and deep solonchakous (endoprotosalic) soils passed to a phase of salt leaching at the present. Horizons with soluble salts moved deeper from the layer 0–100 cm in 1990-s to the layer 100–200 cm in 2010-s. Soils have become very deep solonchakous (bathyprotosalic) with weak and moderate degree of salinity predominantly chloride-sulfate and sulfate composition of salts. Under current conditions, the application of the multispectral satellite information did not allow us to map the salinized soils on the investigated massive. Therefore, maps of salinity in the layers 0–100 and 100–200 cm were created by interpolation method (the method of Inverse Distance Weights) on the basis of experimental data obtained during field investigation in 2015 and 2016. The high content of toxic salts was revealed in soils at the western part and locally in the northern part of Svetloyar Irrigated Massive. These territories will be potentially the most hazardous for secondary salinization, if ground water level rises up (higher than 3 m).